Application of the lean tool Value Stream Mapping (VSM) in the rationalization of the production process in a lubricants and degreasers company - Luciano, Erik Leonel; Ribeiro, Rosinei Batista; Formigoni, Alexandre; Pinho, Alexandre Ferreira de; Bessa, Marcos Antonio (Brazilian Journal of Production Engineering, 2024)
The objective of this study is to analyze and propose improvements in the production process of an industry that manufactures lubricants and degreasers, using the Lean tool known as Value Stream Mapping (MFV). The research was conducted through a case study, following steps such as team formation, selection of the product family, immersion, mapping of the current MFV and development of the rationalized future MFV. The approach adopted was both qualitative and quantitative. The results revealed opportunities for improvement, including the consolidation of the water insertion and raw material mixing steps, resulting in a potential reduction of up to 63.50% in time/cost (T/C). In addition, several other improvement proposals were suggested through the 5W1H kaizen action plan, without the need for large investments.
Keywords: Value Stream Mapping; Lean Manufacturing; Kaizen; Rationalization